Anomalous Dressing of Dirac Fermions in the Topological Surface State of Bi2⁢Se3, Bi2⁢Te3, and Cu-Doped Bi2⁢Se3 - Kondo, Takeshi (2013)
Quasiparticle dynamics on the topological surface state of Bi2⁢Se3, Bi2⁢Te3, and superconducting Cu⁢Bi2⁢Se3 are studied by 7 eV laser-based angle resolved photoemission spectroscopy. We find strong mode couplings in the Dirac-cone surface states at energies of ∼3 and ∼15–20  meV associated with an exceptionally large coupling constant of ∼3, which is one of the strongest ever reported for any material. This result is compatible with the recent observation of a strong Kohn anomaly in the surface phonon dispersion of Bi2⁢Se3, but it appears that the theoretically proposed “spin-plasmon” excitations realized in helical metals are also playing an important role. Intriguingly, the ∼3  meV mode coupling is found to be enhanced in the superconducting state of Cu⁢Bi2⁢Se3.